Proposed business strategy for pt pertamina retail in motorcycle fuel market in jabodetabek area - Nur Hafiz, Dimas; P.K. Bintoro, Bambang (The Indonesian Journal of Business Administration, 2019)
Abstract - The high number of vehicles and daily fuel consumption make a high competition in Indonesian fuel retail industry, this is because there are several companies that sell fuel products in Indonesia, and among them is Pertamina Retail. All companies try to dominate the market share with their own strategies and products. Affordable product prices and a strong brand make Pertamina Retail sales quite high compared to competing companies. However, a high level of sales and a strong brand image is not enough to make Pertamina Retail the first choice of customers. There are several other aspects that become a viewpoint for customers to buy fuel. Therefore, the purpose of this final project is to analyze and create a new competitive strategy so that Pertamina Retail can have a sustainable competitive advantage. The analysis in this final project uses mixed methods, qualitative and quantitative. The quantitative method is conducted by using questionnaires for fuel consumers to obtain the information about the current view of Indonesian fuel customers. Qualitative methods are used to obtain the information by interviewing the company management. Then, there are several analytical tools that will be used to understand the internal and external conditions of Pertamina Retail. PESTEL and Porter’s Five Forces are used to understand external conditions, while the CSF (Critical Success Factors) is used to understand internal conditions. Furthermore, the SWOT analysis tool is used as a summary of the internal and external analysis.The author uses TOWS matrix and Diamond Strategy Model to create a new business strategy that will be recommended to Pertamina Retail. The new business strategy will focus on developing service offerings, after-sales service systems, and improve gas station’s quality to increase customer satisfaction.